The importance of country-of-origin information and perceived product quality in Uzbekistan - Zain, Osman M.; Yasin, Norjaya Mohd (MCB University Press, 1997)
There has been a proliferation of studies on product perceptions based on the country of origin. Most of these studies were conducted in western or developed countries. Studies in the less developed nations are still scarce, especially research conducted in the former Soviet Union. With the disintegration of the Soviet Union, the former Soviet republics offer vast new market opportunities for businesses. However, successful marketing can only be achieved through knowledge about the market, including perceptions of imported products. Aims to contribute to the limited knowledge about market expectations in the former Soviet republics, specifically Uzbekistan. Gathers information on country-of-origin perspectives with regard to product perceptions and importance of product origin information. Based on data collected through personal interviews in Tashkent, the capital city of Uzbekistan.